Trust evaluation routing protocol to enforce cooperation in mobile ad hoc networks - Zhi-jun XU; Qi HU; Yu-jun ZHANG; Xin-ming YE (Tongxin xuebao)
Mobile ad hoc networks(MANET)were based on the assumption that all participants cooperate and forward packets for others.Unfortunately,selfish nodes might be not willing to cooperate and refuse to forward packets.A trust evaluation routing protocol based on DSR (TDSR) was proposed to enforce cooperation and encourage forwarding packets in MANET.The trust value was used to evaluate packet forwarding behaviors.The nodes with low packet forwarding rate were excluded by the node and path trust evaluation.These nodes must wait some time for recovery.Simulation results show that TDSR has obviously higher packet delivery ratio than DSR in face of non-cooperated nodes at the expense of the performance degradation on the delay.